Middle Cerebral Artery Doppler Changes following Fetal Transfusion Performed with and without Fetal Anesthesia - Uquillas, Kristen R.; Aboudiab, Myrna S.; Korst, Lisa M.; Llanes, Arlyn; Grubbs, Brendan H.; Chmait, Ramen H. (American Journal of Perinatology, 2018)
Objective The objective of this study was to test the association between fetal intravenous anesthesia and the change in middle cerebral artery peak systolic velocity (MCA-PSV) in patients undergoing intrauterine transfusion (IUT) for suspected fetal anemia.Study Design We retrospectively examined data from all patients who underwent IUT via umbilical cord route from 2007 to 2016. We calculated the change of the MCA-PSV multiple of median (MoM) as the difference in MCA-PSV MoM between the pre- and immediate postoperative measurements for the first IUT. The change in MCA-PSV MoM was compared between those who did and did not receive fetal anesthesia using Kruskal–Wallis' testing.Results Of 62 patients, 37 (59.7%) received intravenous fetal anesthesia and 25 (40.3%) did not. The change in MCA-PSV MoM did not differ between those who did and did not receive fetal anesthesia (median: 0.57 [interquartile range, IQR: +0.42 to +0.76] vs. median 0.57 [IQR: +0.40 to +0.81], p = 1.000). The relationship remained insignificant when stratifying by gestational age, length of procedure, initial MCA-PSV, and when excluding hydropic fetuses.Conclusion Among women undergoing IUT, there was no evidence that the use of fetal anesthesia was associated with a change in the pre- versus postoperative change in MCA-PSV MoM.
Keywords: fetal anesthesia; Doppler; fetal transfusion